Efficacy and Safety of Conversion Therapy by Intraperitoneal and Intravenous Paclitaxel Plus Oral S-1 in Gastric Cancer Patients With Peritoneal Metastasis: A Prospective Phase II Study - Yang, Zhong-Yin; Yuan, Fei; Lu, Sheng; Xu, Wei; Wu, Jun-Wei; Xi, Wen-Qi; Shi, Min; Wang, Zhen-Qiang; Ni, Zhen-Tian; He, Chang-Yu; Yao, Xue-Xin; Zheng, Ya-Nan; et al. (Frontiers in Oncology, 2022)
Background: Neoadjuvant intraperitoneal and systemic chemotherapy (NIPS) has shown promising results in gastric cancer (GC) with peritoneal metastasis. However, clinical practice experience of NIPS is still lacking in China. In this study, we investigate the efficacy and safety of NIPS in Chinese population. Methods: Eligible patients received NIPS every 3 weeks. Gastrectomy was performed for patients who met the criteria of conversion surgery. The primary end point was 1-year overall survival (OS) rate. Secondary end points were the response rate, toxic effects, conversion surgery outcomes and median survival time (MST). Results: Sixty-seven patients were enrolled. The primary endpoint was met with 1-year OS rate was 67.2% (95% CI, 56.8%-79.4%). Conversion surgery was performed in 42 patients (62.9%), and R0 resection was achieved in 23 patients (54.8%) with the MST of 31.3 months (95% CI, 24.3-38.3). And the MST was 19.3 months (95% CI, 16.4-22.2) for all patients. Toxicity and surgical complications were well-tolerated. Moreover, sex, R0 resection, pathological nodal stage and tumor regression grade (TRG) were independent prognostic factors for patients who underwent conversion surgery. Conclusion: The NIPS is effective and safe in treating GC patients with peritoneal metastasis. Male patients, patients who underwent R0 resection, patients with ypN0-1 or TRG 1 after conversion surgery are more likely to benefit from the NIPS. Clinical Trial Registration: http://www.chictr.org.cn/, identifier ChiCTR2200056029.